Case report of kabuki syndrome in a newborn caused by KMT2D gene mutation - Ba, Xuejiao; Yang, Xiyao; Zhang, Yizhi; Guo, Fang; Zhu, Lihong; Tong, Rui; Yang, Yanbin; Qian, Yuan; Zhang, Hongqing (Frontiers in Pediatrics, 2024)
Background: Kabuki syndrome is a genetic syndrome that affects multiple organs and systems. Gene mutations are the main cause of KS. Mutations in the KMT2D and KDM6A genes have been reported as two relatively clear pathogenic pathways. This article reports a case of KS with congenital heart disease, hearing abnormalities, and hypoglycemia caused by a KMT2D gene mutation confirmed by clinical exome sequencing, enriching the clinical phenotype and gene mutation spectrum of KS and helping to improve understanding of the disease.Case presentation: Through clinical exome sequencing, we performed genetic diagnosis on a newborn with congenital heart malformation and identified a heterozygous mutation in the KMT2D gene (NM_003482.3:c.4195C>T, p.Gln1399*), which has not been reported as a pathogenic mutation before. This variant was not detected in the peripheral blood of the patient's parents, suggesting it is a de novo mutation.Discussion: KS has strong clinical characteristics and biological heterogeneity. Genetic diagnosis can help identify the types of mutated genes. Our results provide some clues for KS caused by KMT2D gene mutations associated with congenital heart disease, hearing abnormalities, and hypoglycemia. However, the relationship between genotype and phenotype is not yet fully understood. The molecular pathogenesis of KS still needs further exploration and clarification.